Evaluating the efficiency of public services - Geraint Johnes (IZA World of Labor, 2015)
Efficiency is an important consideration for those who manage public services. Costs vary with output and with a variety of other factors. In the case of higher education, for example, factors include quality, student demographics, the scale and scope of the higher education provider, and the size and character of the real estate. But even when taking all these factors into account, costs vary across providers because of differences in efficiency. Such differences offer clues about good practice that can lead to improvements in the system as a whole. The role of efficiency is illustrated by reference to higher education institutions in England.
Keywords: C40; D24; H42; H44; I20; I23; 330; efficiency; costs; higher education